2023
DOI: 10.1108/ijshe-07-2022-0234
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment model for students’ sustainability: evidence from a Peruvian university

Abstract: Purpose The study of sustainability within universities is recognized as essential for debates and research; in the long term, the “sustainable university” concepts can contribute to sustainability from a larger perspective. This study aims to propose a conceptual model for evaluating the students’ sustainability considering their interactions with the university and the environment. The proposed model is titled Sunshine model. It is applied to students of the La Salle University, Peru. Design/methodology/ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
1
1
0
Order By: Relevance
“…Regarding specific research dimensions, it was observed that students value hands-on experience and the literature review process, consistent with the idea that a literature review is a pivotal stage in any research process (Giannetti et al, 2023). However, the more critical perceptions about universities' actions and research parameters suggest that students might feel that institutions are not providing enough support or finding certain parameters restrictive, aligning with the concept that attitudes are not formed in a vacuum but are shaped by experiences and expectations (Fox et al, 2023).…”
Section: Discussion Of Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Regarding specific research dimensions, it was observed that students value hands-on experience and the literature review process, consistent with the idea that a literature review is a pivotal stage in any research process (Giannetti et al, 2023). However, the more critical perceptions about universities' actions and research parameters suggest that students might feel that institutions are not providing enough support or finding certain parameters restrictive, aligning with the concept that attitudes are not formed in a vacuum but are shaped by experiences and expectations (Fox et al, 2023).…”
Section: Discussion Of Resultssupporting
confidence: 68%
“…This approach provides context, prevents duplicate efforts, and allows the researcher to identify gaps in existing knowledge. Students' attitudes toward material reviews can be influenced by several factors (Giannetti et al, 2023). These encompass the accessibility of sources, the perceived relevance of material, and the ability to synthesize and critically analyze information.…”
Section: Dimension 6: Attitude Toward Reviewing Research Materialmentioning
confidence: 99%